1987
DOI: 10.1128/mcb.7.5.1629
|View full text |Cite
|
Sign up to set email alerts
|

c-mos proto-oncogene RNA transcripts in mouse tissues: structural features, developmental regulation, and localization in specific cell types.

Abstract: c-mos RNA transcripts have been previously detected in mouse gonadal tissue and in late-term embryos. Here, we show that they are also present at low levels in placenta and in adult mouse brain, kidney, mammary gland, and epididymis. Marked differences are observed in the size of the mos RNA transcripts detected in different tissues. All transcripts appear to end at the same 3' position, and the tissue-specific size variations appear to be due to the use of different promoters. For example, the testicular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
71
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(74 citation statements)
references
References 42 publications
3
71
0
Order By: Relevance
“…The size difference is apparently due to tissue-specific utilization of different promoters. In the testis, the transcription initiation sites are clustered around -280 bp, while in the ovary they have been mapped to around -70 bp with respect to the first ATG of the c-mos open reading frame (30). Neither of the two promoter regions contain TATA boxes, GC-rich tracts, or other identified transcriptional regulatory sequences.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The size difference is apparently due to tissue-specific utilization of different promoters. In the testis, the transcription initiation sites are clustered around -280 bp, while in the ovary they have been mapped to around -70 bp with respect to the first ATG of the c-mos open reading frame (30). Neither of the two promoter regions contain TATA boxes, GC-rich tracts, or other identified transcriptional regulatory sequences.…”
mentioning
confidence: 99%
“…Si nuclease analysis has indicated that c-mos produces 1.7-and 1.4-kb transcripts in mouse testis and ovary, respectively (30,31). The size difference is apparently due to tissue-specific utilization of different promoters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While some protooncogenes are expressed in many cell types, others display more restricted patterns of expression, suggesting that they play a role in particular developmental schemes. c-mos is unique among the protooncogenes in that its major sites of expression appear limited to male and female germ cells of the mouse and of several other species (1)(2)(3)(4)(5)(6)(7)(8), suggesting a specific function for c-mos in meiotic cell types.…”
mentioning
confidence: 99%
“…Its cellular homolog, c-mos, is also capable of transforming ®broblasts when placed under the control of long terminal repeat (LTR) sequences of Mo-MSV (Blair et al, 1981;Oskarsson et al, 1980). Relatively high levels of c-mos mRNA expression have been found in germ cells from a variety of vertebrates while much lower levels of expression have been detected in some somatic tissues (Goldman et al, 1987;Herzog et al, 1988Herzog et al, , 1989Keshet et al, 1988;Li et al, 1993;Mutter and Wolgemuth, 1987;Propst et al, 1987;Propst and Vande Woude, 1985;Sagata et al, 1988;Tsui et al, 1993). Mos has been shown to have a critical role in oocyte maturation as demonstrated by the phenotype of mos de®cient (knockout) mice (Colledge et al, 1994;Hashimoto et al, 1994).…”
Section: Introductionmentioning
confidence: 99%